IMPROVING THE STUDENTS’ WRITING NARRATIVE TEXT BY APPLYING COOPERATIVE INTEGRATED READING AND COMPOSITION TECHNIQUE - Marhamah Melisda (Universitas Negeri Medan, 2014)
Abstract This study concerrns with Improving the Students Writing Narrative Text by Applying Cooperative Integrated Reading and Composition Technique.The objective was to investigate improvement of students’ writing narrative text by applying Cooperative Integrated Reading and Composition Technique. This research was conducted by using action research method. The subject of the study was grade VIII students of MTS Al- Hasanah Medan totalling to 29 students. They were taught writing by cooperative integrated reading and composition technique. The instruments for collecting data were quantitative data and qualitative data (observation sheet, questionnaire sheet, and interview sheet). Based on the test score of quantitative data, students’ score kept improving in every evaluation. In the orientation test the mean was 43, 2, in the cycle I test the mean was 55, 6. In the cycle II test the mean was 67.2. The percentage of orientation test was 10, 34%, cycle I test was 24, 13% and cycle II test was 86, 20%. The finding of the research showed that applying Cooperative Integrated Reading and Composition Technique significantly improved students’ writing. The qualitative data show that the students were more interested and motivated on writing through cooperative integrated reading and composition technique. It is suggested that teachers should apply cooperative integrated reading and composition technique as one of methods to improve students’ writing. Keywords: Classroom Action Research, writing, Cooperative Integrated Reading and Composition Technique,narrative text.